Synergistic impact of integrated mechanical, physical, and chemical disinfection on microbial ecology and morphophysiological development in dairy calves - K. Shaikenova; S. Issabekova; M. Sadenova; K. Omarova; R. Uskenov (Brazilian Journal of Biology)
Abstract The article presents the results of studies of the influence of the complex process of cleaning and disinfection of the dispensary using mechanical, physical and chemical methods on the growth and development of calves of the dairy period. The dispensary for calves is divided into two rooms, where there were animals of the control and experimental groups selected by the method of pairs of analogues in the same feeding and maintenance conditions. Studies before the treatment of rooms for calves showed a massive growth of bacilli and bacteria – 100%, mold fungi – 80%, yeast - 20%, actinomycetes – 80%. After processing the room for calves of the experimental group, the number of microorganisms during mechanical treatment, microbial contamination decreased by 31%, during physical treatment by 62%, and during chemical treatment by 95%. Monitoring of live weight, exterior features of calves showed that the live weight of calves of the experimental group of monthly calves averaged 58.9 kg, and the control group 58.6 kg, respectively. In the second month, the live weight of the experimental was 7.5 kg or 9.1% more than the control. And also for all body measurements, the experimental group exceeded the control group by an average of 10%. The results of the study of hematological parameters showed that in the experimental group they are all within the normal range, whereas in the control group the content of leukocytes is 13.2 * 109 liters, lymphocytes are 7.7 * 109 liters higher than normal, which indicates inflammatory processes in the body of calves.